Pavel Rennenkampf: Unnoticed Decembrist Conspirator - P. V. Ilyin (Научный диалог)
This article addresses the misidentification of Colonel Pavel Rennenkampf, a member of the Southern Decembrist conspiracy and a colonel in the General Staff (1790-1857), by historians. Through the examination of investigative materials, police reports, official correspondence, and memoirs, the author aims to establish the documentary evidence supporting Pavel Rennenkampf’s involvement in the Decembrist movement. It is concluded that this officer played a significant role in S.I. Muravyov-Apostol’s plans for organizing the uprising of the Chernigov Regiment, dedicated to the secrecy of the military conspiracy and its political goals. The research novelty lies in shedding light on an understudied figure in Decembrist history, previously overlooked by historiography. The relevance of this study lies in its contribution to understanding key events in the Decembrist movement — the Southern conspiracy and uprising. The article discusses why the incriminating evidence indicating P.Ya. Rennenkampf's involvement in clandestine societies was dis-regarded during historical proceedings and remained largely unnoticed by historians. The author provides an explanation for the long-standing misattribution of K.P. Rennenkampf instead of P.Ya. Rennenkampf in historical accounts.